Appetite for destruction: E3 ubiquitin-ligase protection in cardiac disease. (January 2008) - Willis, Monte S; Schisler, Jonathan C; Patterson, Cam
Over the course of 3 billion heartbeats in an average human lifetime, the heart must maintain constant protein quality control, including the coordinated and regulated degradation of proteins via the ubiquitin-proteasome system (UPS). Recent data highlight the specificity by which the UPS functions in the context of cardiac hypertrophy, ischemic heart disease and cardiomyopathies. Although curbing the appetite of the proteasome through the use of inhibitors in animal models of cardiac disease has proven effective experimentally, recent studies report proteasome inhibition as being cardiotoxic in some patients. Therefore, focusing on specific regulatory components of the proteasome, such as members of the E3 ubiquitin-ligase family of proteins, may hold promise for targeted therapeutics of cardiac disease. This review focuses on the UPS, its specific role in cardiac disease and opportunities for novel therapies.